EFFECTIVITY OF CINNAMON (Cinnamomum burmanii) TO DECREASE UREA LEVELS - Evi Lusiana; Nia Savitri Tamzil; Desi Oktariana; Indri Seta Septadina (International Islamic Medicine Forum, 2022)
Urea or Blood Urea Nitrogen (BUN) is a non-protein blood nitrogen molecule that results from the catabolism of protein and amino acids through the urea cycle and is eliminated by the kidneys as urine, perspiration, and degraded by intestinal bacteria. BUN levels can indicate renal disease. Cinnamon (Cinnamomum burmanii) is an Indonesian herb that functions as an anti-inflammatory and antioxidant, reducing urea levels and contributing to improved kidney function. The search was conducted using Google Scholar, Pubmed, and Science Direct.